Seated single-arm shot-put test to measure the functional performance of the upper limbs in exercise practitioners with chronic shoulder pain: A reliability study - Pinheiro, J. S.; Lima Soares Monteiro, O.; Brito Pinheiro, C. A.; Brenha Penha, L. M.; Quixabeira Guimarães Almeida, M.; Bassi-Dibai, D.; de Oliveira Pires, F.; Torres Cabido, C. E.; Fidelis-de-Paula-Gomes, A.; Vieira Dibai-Filho, A. (Journal of Chiropractic Medicine, 2020)
Objective: To measure the intra- and interrater reliability of the seated single-arm shot-put test (SSPT) in the functional performance of the upper limbs of regular physical exercise practitioners with shoulder pain. Methods: This is a reliability study. Thirty individuals regularly practicing any sports modality that uses the upper limb effectively for at least 6 months, both sexes, ages between 18 and 30 years, with chronic shoulder pain were included. Chronic shoulder pain was measured by means of the shoulder pain and disability index, numerical rating scale, and catastrophic thoughts about pain scale. Functional performance of the upper limbs was measured by means of SSPT. Results: Excellent intrarater reliability was found, with intraclass correlation coefficient =0.93, standard error of the measurement values =4.63%, and minimum detectable change values for absolute and normalized score of 45.11 cm and 9.97, respectively. Excellent interrater reliability was found, with intraclass correlation coefficient =0.96, standard error of the measurement values =3.55%, and minimum detectable change values for absolute and normalized score of 32.29 cm and 7.70, respectively. Conclusion: SSPT is a reliable tool for measuring the functional performance of the upper limbs in regular exercise practitioners with chronic shoulder pain.